(untitled) (Journal of Nuclear Technology in Applied Science, 2026)
This study investigates the enhancement of carboxymethyl cellulose (CMC)/ glycerol (Glyc) edible coatings through gamma irradiation (0, 1, 2, and 3 kGy) to extend the shelf life of fresh cucumbers. Analytical characterization using Fourier Transform Infrared (FTIR) confirmed that the primary functional groups of the CMC matrix remained stable following irradiation. Thermal evaluations via Thermogravimetric Analysis (TGA), Differential scanning calorimetry (DSC), and Thermomechanical Analysis (TMA) revealed that a 2 kGy dose provided an optimal for thermal stability due to radiation-induced cross-linking. Physicochemical results showed that irradiated coatings (3 kGy) significantly outperformed unirradiated controls in preserving quality throughout a 28- day storage period. Rheological analysis indicated that irradiation reduced the apparent viscosity of the CMC/Glyc solutions due to the cleavage of glycosidic bonds, which improved application characteristics. Furthermore, microbiological testing demonstrated that the 3 kGy irradiated coating acted as a potent antimicrobial agent.